2006
DOI: 10.1111/j.1556-4029.2006.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of Drug and Alcohol Use in Fatally Injured Drivers in Washington State

Abstract: We have previously reported on patterns of drug and alcohol use in fatally injured drivers in Washington State. Here we revisit that population to examine how drug use patterns have changed in the intervening 9 years. Blood and serum specimens from drivers who died within 4 h of a traffic accident between February 1, 2001, and January 31, 2002, were analyzed for illicit and therapeutic drugs and alcohol. Drugs when present were quantitated. Samples suitable for testing were obtained from 370 fatally injured dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 27 publications
1
39
0
3
Order By: Relevance
“…Although it is difficult to draw comparisons between exposures in humans and mice, in our previous work exploring lung injury after exposure to 25 to 100 mg MA, the doses of MA causing lung injury resulted in plasma MA levels that were well below the mean MA plasma level of 730 ng/ml reported for MA users (21). However, it is likely that the findings in our initial study more closely modeled the respiratory effects expected to be seen in MA users rather than in environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to draw comparisons between exposures in humans and mice, in our previous work exploring lung injury after exposure to 25 to 100 mg MA, the doses of MA causing lung injury resulted in plasma MA levels that were well below the mean MA plasma level of 730 ng/ml reported for MA users (21). However, it is likely that the findings in our initial study more closely modeled the respiratory effects expected to be seen in MA users rather than in environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…They are also used as muscle-relaxants and anti-convulsants. They are often detected in incidents of driving under the influence of drugs (DUID) and in combination with other medications (2,3). Oral fluid is becoming increasingly used as a specimen in many areas of forensic and clinical interest, including collection at the roadside during traffic stops.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies on apprehended drivers shed light on this adverse effect of carisoprodol. First, a case series by Logan and co-workers indicated that carisoprodol by itself could cause traffic related impairment with blood drug concentrations within the range observed with normal therapeutic use (36,37). Second, an analysis of secular trends from our group showed that drivers using carisoprodol were stopped by the police and that the number of drivers related closely to the amount of carisoprodol sold to the population (38).…”
Section: Psychomotor Impairmentmentioning
confidence: 87%